The Effect of Hedonic Shopping Value on Impulse Buying with Positive Emotion as an Intervening Variable on Tokopedia Consumers - Hari, Abdulhadi (Universitas Dian Nuswantoro Semarang, 2025)
In the current digital era, online shopping has become an increasingly popular phenomenon, dominating people's consumption patterns. One of the leading e-commerce platforms in Indonesia is Tokopedia, offering a wide range of products and services to its consumers and providing a comfortable and easy shopping experience. This research utilizes a quantitative approach, as the researcher suspects a direct effect of Hedonic Shopping Value on Impulse Buying. Positive Emotion acts as a mediating variable between Hedonic Shopping Value and Impulse Buying. The estimated parameter value of the regression weight coefficient is 0.237, and the CR value is 2.409, indicating a relationship between Hedonic Shopping Value and Impulse Buying. This suggests that the stronger the influence of Hedonic Shopping Value, the more Positive Emotion will increase. The significance test shows a probability value of 0.016 (p < 0.05), indicating that